Punchdrunk’s Immersive Theatre: From the End to the Edge - Deborah Prudhon (Sillages Critiques)
Immersive theatre appears to be a flourishing trend on the contemporary British scene. The events which are labelled as such all share the intention of “[placing] the audience at the heart of the work” (Josephine Machon) and abolish the distinction between stage and auditorium to merge them into one single space. This type of theatre questions not only the status of the spectator, redefining his/her place and role, but also the notion of ending. This article examines the work of the British company Punchdrunk which can be considered a “pioneer” in the field and which creates expansive environments that the “immersants” are free to explore as they wish. In these shows, the spectators are no longer placed in front of a narrative unfolding in a linear way with a beginning, a middle and an end. Invited to roam free through the performance space, they take individual journeys and discover the different scenes as they go along and happen to come across them. Such a radical change of perspective invites us to reconsider the very notion of ending and to think of it not so much in temporal terms, as the last stage in a teleological progression, but to look at it from a spatial angle. The driving force of the shows itself reveals a shift from the temporal to the spatial: “The moment-to-moment ‘what happens next?’ of conventional narratives is replaced by the ‘where is he going?’ and ‘what’s in the next room?’” (Gareth White). The end of the game, therefore, is not to passively wait for the narrative to unfold to its end, but to actively explore this terra incognita in an attempt to reach its edges. As the size of the performance space makes it impossible to see it all in one night, the temporal end of the show is inevitably frustrating for the immersants. They tend to gather — physically or online — after the performance in order to share their respective experiences, to try and piece together the narrative puzzle and map out the space. Punchdrunk’s shows thus go beyond their temporal boundaries and one can wonder when — and if — the immersive adventure truly ends.